Решите уравнение : (х-3)(х(в квадрате ) +3х + 9 ) - х (х+5)(х-5)=23 и решите 4х (х+4) + х (в кубе ) + 64 = 0

kurotetsu666 kurotetsu666    2   18.05.2019 01:40    0

Ответы
maksarowa1980 maksarowa1980  11.06.2020 06:31

х(в кубе)+3х(в квадрате)+9х-3х(в квадрате)-9х-27-х(в кубе)+25х=23,

25х=27+23,

25х=50,

х=2

ответ:2

ПОКАЗАТЬ ОТВЕТЫ
bomberdire bomberdire  11.06.2020 06:31

4x^{2}+16x+x^{3}+64=0\\ x^{2}(4+x)+4(x+4)=0\\ (x^{2}+4)(x+4)=0\\ x^{2}+4=0 нет корней

4+x=0\\ x=-4  - это ответ 

здесь только один корень

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра